Cultivo, composição química e biologia floral de Varronia curassavica Jacq. - Debora Soares Brandao (2014)
Varronia curassavica Jacq. is a Brazilian native species, with antiinflammatory medicinal property. It has a scientifically recognized effectiveness. From the essential oil of the species is produced an important anti-inflammatory phytotherapic. Knowing the culture conditions of a medicinal species is important in their conservation and in the sustainable production. And, being a native species, knowledge of the reproductive system is essential for the conservation and management of the species. Thus, the objectives of the present research were to evaluate the biomass, the content and the production of the essential oil and its chemical characterization and quantification of -humulene and of the -caryophyllene, besides determine the floral morphometric characteristics, phenology of flowering, the anthesis, visitors insects and the determination of the reproductive system of whaling herb in a germplasm collection. The experiment was conducted at the Institute of Agricultural Sciences of the Federal University of Minas Gerais (ICA/UFMG), Montes Claros-MG. It was used a randomized block design in a 2x2 factorial design (two spacings - 1.6 x 0.5 m and 1.0 x 0.5 m x with and without mulch), with five replications and 12 plants per plot. After 168 days of cultivation were evaluated: height, stem diameter, fresh matter, dry matter, content and production of the oil and its chemical characterization. The essential oil was extracted by hydrodistillation and analyzed by gas chromatography coupled with mass spectrometer (GC / MS). For the morphometric characteristics were used 20 flowers, from five individuals in pre-anthesis, collected from stock plants existing in the germplasm collection of the species in the Medicinal Horto of ICA / UFMG. Between May and December 2012, it was characterized the phenologic behavior of the flowering of six individuals. In the analyzes of floral phenology were determined the growth of inflorescence, number of flowers and fruits, the opening period, the floral visitors and the reproductive system. To determine the reproductive system, it was used the pollen: ovule ratio (P:O) in 50 flowers. For the essential oil content and the fresh matter, the smallest spacing with mulch and the wider spacing without mulch resulted in the highest significant averages. In the production of oil, the smallest spacing with mulch was significant. For dry matter, only the smallest spacing was significant. There was no significant difference to height and diameter. The concentrations of the -humulene and of the -caryophyllene were not significantly different between the treatments. Regarding the floral morphology, the flowers presented a diameter of 2.13 ± 0.05 (mm), length 3.29 ± 0.08 (mm), ovarian diameter of 0.70 ± 0.02 (mm), ovarian length of 2.48 ± 0.12 (mm), diameter of the anther of 0.67 ± 0.01 (mm) and anther length of 0.93 ± 0.02 (mm), with four ovules and five anthers. In the conditions of the present study, the growth of inflorescences from ervabaleeira occurred between August and October. The flowering was observed between September and October, and the fruiting from October to December. The floral anthesis occurred between 7:00 and 11:00 hours. The visitor insects are from the orders Coleoptera, Hemiptera, Diptera and Hymenoptera. The species has been classified in the conditions of the study like facultative alogamous.